Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1038/sj.gt.3301494
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for nonspecific adsorption of targeted retrovirus vector particles to cells

Abstract: The ability to specifically target a cell-type is important for the development of vectors for in vivo gene therapy. In order to produce retrovirus vectors targeting ovarian cancer cells, which specifically overexpress ␣ folate receptor (␣FR), a single chain antibody was fused as an N-terminal extension of the ecotropic and amphotropic murine leukemia virus (MLV) envelope glycoproteins. Vector particles bearing the modified glycoproteins were produced and analysed. Although conventional FACS studies indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 29 publications
5
45
0
Order By: Relevance
“…These kinetics suggest that the transduction efficiency among secondary target cells is the result of an evolving equilibrium between sustained release by carrier cells and the half-life of particles in culture at 37°C. In agreement with the literature, particle retention and release are not Env pseudotype restricted, and we show similar magnitudes of transfer and secondary transduction for amphotropic, ecotropic, and VSV-G pseudotype vector particles, adjusted for vector titer (30,31). We also confirmed that the transduction of secondary target cells is only moderately sensitive to vector exposure duration and is not limited to the relatively brief exposure (1 h) in our experimental protocol, again consistent with studies by Cole (10).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These kinetics suggest that the transduction efficiency among secondary target cells is the result of an evolving equilibrium between sustained release by carrier cells and the half-life of particles in culture at 37°C. In agreement with the literature, particle retention and release are not Env pseudotype restricted, and we show similar magnitudes of transfer and secondary transduction for amphotropic, ecotropic, and VSV-G pseudotype vector particles, adjusted for vector titer (30,31). We also confirmed that the transduction of secondary target cells is only moderately sensitive to vector exposure duration and is not limited to the relatively brief exposure (1 h) in our experimental protocol, again consistent with studies by Cole (10).…”
Section: Discussionsupporting
confidence: 74%
“…However, not all binding after ex vivo exposure leads to cell entry, nuclear translocation, and proviral integration. Attachment of virus particles to the target cell surface can be nonspecific, without the requisite binding to a specific receptor or cellular uptake (30,31,35,36). Such nonspecific binding is of considerable magnitude in vitro and likely contributes to dilution effects and limited target cell transduction efficiency after in vivo particle delivery (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although receptor binding was observed, this vector was not able to induce gene expression. Similar results were observed for a MLV vector bearing a single chain anti-folate receptor antibody to produce vectors targeting ovarian cancer cells (Pizzato et al, 2001), manifesting the limitations of folate receptor targeting. A modification of this approach combines genetic modification of the GP by inclusion of an IgG-binding domain and the conjugation with an antibody that reacts with specific cell surface molecules expressing the antigen (Ohno et al, 1997).…”
Section: Non-genetic Retroviral Targetingsupporting
confidence: 64%
“…4,5 This stems, in part at least, from virus neutralization, nonspecific adhesion of the virus particles to multiple host cell types and from active sequestration of particles. 4,[6][7][8][9] A further problem is the inability to localize viruses specifically to tumors and to promote their extravasation from the circulation. 10 In this latter respect, extensive preclinical and clinical studies have shown that tumors are often infiltrated with T cells with specificity for antigens expressed by the tumor cells themselves.…”
Section: Introductionmentioning
confidence: 99%